Efforts to Handle and Prevent Trademark Infringement in E-Commerce Business in Indonesia - Indrawati, Etty; Susilawati, Marietta D.; Handoyo, Richard Willie (Westscience Press, 2025)
The development of technology, especially the presence of e-commerce platforms, has facilitated the interaction between sellers and buyers. This raises challenges, one of which is the potential for trademark infringement in e-commerce platforms. This can harm the owner/holder of the rights to the trademark economically because of the potential damage to the product image represented by the trademark used by other parties without rights. This research aims to identify efforts to handle and prevent trademark infringement in e-commerce businesses in Indonesia. The method used in this research is normative juridical and is supported by interviews with resource persons. The data used in this research is secondary data consisting of primary legal materials in the form of statutory instruments, and secondary legal materials consisting of scientific papers and other research results. The analysis in this research is done qualitatively. The results of the research conclude that efforts can be made to face the challenges of trademark infringement in e-commerce business in Indonesia to protect the exclusive rights of trademark owners/holders.